Biochemical and structural investigations of Bothropstoxin-II, a myotoxic Asp49 phospholipase A(2) from Bothrops jararacussu venom - Murakami, Mario T. [UNESP]; Lourenzoni, Marco R.; Arruda, Emerson Z.; Tomaz, Marcelo A.; Vicoti, Magno M. [UNESP]; Abrego, Jose R. B. [UNESP]; Melo, Paulo A.; Arni, Raghuvir K. [UNESP] (Bentham Science Publ Ltd, 2008)
Bothropstoxin-II a calcium-dependent enzyme from Bothrops jararacussu venom causes tissue damage and several haemostatic disorders including platelet aggregation. In order to elucidate the structural determinants of its multiple pharmacological activities, we have studied the effects of suramin on Bothropstoxin-II and present details concerning the mode of binding.
Keywords: phospholipases A(2); suramin; pharmacological activities; structural studies